Sudden Cardiac Death in the Young: Incidence, Trends, and Risk Factors in a Nationwide Study. Issue 10 (October 2020) - Ha, Francis J.; Han, Hui-Chen; Sanders, Prashanthan; Fendel, Kim; Teh, Andrew W.; Kalman, Jonathan M.; O'Donnell, David; Leong, Trishe; Farouque, Omar; Lim, Han S.
Abstract : Background: Sudden cardiac death (SCD) in the young is devastating. Contemporary incidence remains unclear with few recent nationwide studies and limited data addressing risk factors for causes. We aimed to determine incidence, trends, causes, and risk factors for SCD in the young. Methods and Results: The National Coronial Information System registry was reviewed for SCD in people aged 1 to 35 years from 2000 to 2016 in Australia. Subjects were identified by the International Classification of Diseases, Tenth Revision code relating to circulatory system diseases (I00–I99) from coronial reports. Baseline demographics, circumstances, and cause of SCD were obtained from coronial and police reports, alongside autopsy and toxicology analyses where available. During the study period, 2006 cases were identified (median age, 28±7 years; men, 75%; mean body mass index, 29±8 kg/m 2 ). Annual incidence ranged from 0.91 to 1.48 per 100 000 age-specific person-years, which was the lowest in 2013 to 2015 compared with previous 3-year intervals on Poisson regression model ( P =0.001). SCD incidence was higher in nonmetropolitan versus metropolitan areas (0.99 versus 0.53 per 100 000 person-years; P <0.001). The most common cause of SCD was coronary artery disease (40%), followed by sudden arrhythmic death syndrome (14%). Incidence of coronary artery disease–related SCD decreased from 2001–2003 to 2013–2015 ( P <0.001). Proportion of SCD related to sudden arrhythmic death syndrome increased during the study period ( P =0.02) although overall incidence was stable ( P =0.22). Residential remoteness was associated with coronary artery disease–related SCD (odds ratio, 1.44 [95% CI, 1.24–1.67]; P <0.001). For every 1-unit increase, body mass index was associated with increased likelihood of SCD from cardiomegaly (odds ratio, 1.08 [95% CI, 1.05–1.11]; P <0.001) and dilated cardiomyopathy (odds ratio, 1.04 [95% CI, 1.01–1.06]; P =0.005). Conclusions: Incidence of SCD in the young and specifically coronary artery disease–related SCD has declined in recent years. Proportion of SCD related to sudden arrhythmic death syndrome increased over the study period. Geographic remoteness and obesity are risk factors for specific causes of SCD in the young. Abstract : Supplemental Digital Content is available in the text.